Thoracolumbar injuries : short segment posterior instrumentation as standalone treatment - thoracolumbar fractures - Davis, Johan, H. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Surgical Sciences. Orthopaedic Surgery))--University of Stellenbosch, 2010.